Unsur-Unsur Komunikasi dalam Dakwah Rasulullah SAW dan Implementasi Strategi Dakwah Rasulullah di Era Digital - Nabil Hibrizi, Azzam (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2024)
Communication is a key element in da'wah, an interactive process that not only demands the delivery of religious messages but also requires an effective approach that suits the needs and context of the audience. This study uses a qualitative approach with descriptive analysis to discuss the elements of communication in da'wah and its implementation in the digital age, revealing the importance of effective strategies in maintaining the authenticity of the da'wah message while meeting the demands of the times. The study reflects on the Prophet's method of da'wah, which combined correspondence, patience, gentleness, and prayer, adjusting strategies based on specific situations and encouraging two-way communication to measure the effectiveness of da'wah. In the digital age, da'wah strategies must adapt to technology without losing the humanist touch and empathy that characterized the Rasulullah SAW when da'wah.